Vertical Integration in the U.S. Pulp and Paper Industry, 1900-1940 - Ohanian, Nancy Kane (The Review of Economics and Statistics, 1994)
A transaction-cost model of vertical integration is tested, based on detailed descriptions of every pulp and paper mill operating in the United States between 1900 and 1940. This study contributes to the literature on integration through the use of a large, disaggregated database that allows identification of individual mills over time. Vertical integration of pulp and paper production is found to be positively associated with regional concentration, paper-mill capacity, and production of standardized grades of paper. Over time, new entrants behaved differently than established mills, because few mills switched between integration and specialization once established. Copyright 1994 by MIT Press.